Posthuman Keats. Poetry as Assemblage (Altre Modernità, 2020)
This article explores the notions of flotsam, jetsam and hybridity inJohn Keats’s poetry in order to provide a critical reading informed byposthumanist theories, and, more specifically, Donna Haraway’s cyborg. It startswith the metaphor of debris and the linguistic-literary metaphor of texture/textus.It then proceeds to elucidate how Keats deals with flotsam and jetsam in hiswork. A short overview of the theory of organic unity begins the last section of thearticle, which focuses on the poet’s penchant for hybrid poetic endeavours andenvisions some of his work as a metaphorical manifestation of the cyborg myth.
Keywords: Keats; posthumanism; cyborg; assemblage; Donna Haraway